Physiological factors affecting platelet-rich plasma variability in human and veterinary medicine - Colomer-Selva, Rocío; Tvarijonavciute, Asta; Franco-Martínez, Lorena; Hernández-Guerra, Ángel María; Carrillo, José María; Rubio, Mónica; Sopena, Joaquín Jesús; Satué, Katy (Frontiers in Veterinary Science, 2025)
Platelet-rich plasma (PRP) is the fraction of autologous plasma that contains a supraphysiological concentration of platelets, which are an important reservoir of growth factors. PRP is today one of the treatments of choice in regenerative medicine in both humans and animals. The aim of this study was to assess the existing literature on the possible influence of the patient’s physiological factors on different PRP characteristics, like platelet concentration, quantity of obtained plasma, quantity and types of growth factors (GFs) in human and veterinary medicines. In addition, a secondary aim was to compare protocols used to prepare PRP in these studies. In a total of 34 studies evaluated, the use of different protocols for the preparation and characterization of PRP and certain physiological factors such as age, sex and body condition substantially modify the characteristics of PRP in both human and veterinary medicine. Therefore, it is essential to standardize PRP collection protocols and define study groups based on physiological factors like sex, age, body mass index, fertility status and analyzed GFs to ensure reliable data and derive precise, informative conclusions.